Lowland rice soils in thailand - Kawaguchi, Keizaburo (The center for Southeast Asian studies, 1969)
Contents: Introduction; methods; samples; morpholical characteristics as "paddy soil"; clay mineralogical characteristics; fertilyty characteristics.